Correlation Between COVID-19 Recovery, Executive Function Decline, and Emotional State - Velásquez Cabrera DM; De la Roca-Chiapas JM; Hernández-González MA; Reyes Pérez V; Villada C (Psychology Research and Behavior Management)
Daniela María Velásquez Cabrera,1 Jose Maria De la Roca-Chiapas,2 Martha Alicia Hernández-González,3 Verónica Reyes Pérez,2 Carolina Villada2 1Health Sciences Division, University of Guanajuato, Guanajuato, Mexico; 2Department of Psychology, University of Guanajuato, Guanajuato, Mexico; 3Department of Medicine and Nutrition, Division of Health Sciences, University of Guanajuato, Guanajuato, MexicoCorrespondence: Jose Maria De la Roca-Chiapas, Department of Psychology, University of Guanajuato, Mexico Sede San Carlos, Blvd. Puente Milenio No. 1001 Fracción del Predio San Carlos; C.P. 37670, León, Guanajuato, Mexico, Tel +52 477 267 4900 ext 3644, Email josema_delaroca@yahoo.com.mxObjective: The aim of this study was to determine whether there is a relationship between the time since recovery from coronavirus disease 2019 (COVID-19) and alterations in executive functions. We also evaluate the emotional state of post-COVID-19 patients.Patients and Methods: We assessed patients between 18 and 50 years old, who had a history of COVID-19 with mild, moderate, or severe illness. We used the Batería Neuropsicológica de Funciones Ejecutivas y Lóbulos Frontales-3 (BANFE-3), Mini-Mental State Examination (MMSE), and Mini-International Neuropsychiatric Interview (MINI), in addition to a semi-structured interview. Spearman’s correlation coefficient was used, with a p value < 0.05 indicating significance.Results: We evaluated 67 patients with a mean age of 34.6± 9.6 years, most of whom had ≥ 13 years of schooling (n=55, 82.1%). Among them, 52 (77.6%) reported persistent symptoms after resolution of the condition, with fatigue being the most frequent (n=20, 29.9%). Most participants had an adequate score on the MMSE (n=60, 89.6%). However, 19 (28.4%) showed alterations in the BANFE-3 total score, with mental flexibility as the most affected function (n=25, 37.3%). In participants from the first COVID-19 wave, a negative correlation was observed between the standardized orbitofrontal area scores and the time since recovery from the infection (r=− 0.841, p=0.016), suggesting a pattern of deterioration over time, mainly in stimulus inhibition (r=0.880, p=0.021). Regarding emotional state, 45 subjects (67.2%) exhibited emotional alterations, with anxiety symptoms being the most frequent (n=33, 49.3%). Furthermore, individuals with depressive symptoms (n=32, 47.8%) were more likely to experience executive function impairment after COVID-19 (ExpB 0.302, 95% CI 0.098– 0.933, p=0.038).Conclusion: COVID-19 could lead to alterations in executive functions, probably resulting from progressive damage to orbitofrontal area functions, mainly in stimulus inhibition. However, the generalizability of these findings is limited, highlighting the need for further research with robust methodology. Furthermore, depression appears to be an indicator of cognitive impairment in individuals recovering from COVID-19. Therefore, cognitive rehabilitation and psychological support are essential for patients affected by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection.Keywords: coronavirus infection, cognition, executive function, affective symptoms